Assessment of the role of afucosylated glycoforms on the in vitro antibody-dependent phagocytosis activity of an antibody to Aβ aggregates. Issue 1 (1st January 2020) - Kwiatkowski, Allyson; Co, Carl; Kameoka, Sei; Zhang, An; Coughlin, John; Cameron, Tom; Chiao, Eric; Bergelson, Svetlana; Schmid Mason, Cullen
ABSTRACT: The terminal sugars of Fc glycans can influence the Fc-dependent biological activities of monoclonal antibody therapeutics. Afucosylated N-glycans have been shown to significantly alter binding to FcγRIIIa and affect antibody-dependent cell-mediated cytotoxicity (ADCC). Therefore, in order to maintain and ensure safety and efficacy for antibodies whose predominant mechanism of action (MOA) is ADCC, afucosylation is routinely monitored and controlled within appropriate limits. However, it is unclear how the composition and levels of afucosylated N-glycans can modulate the biological activities for a recombinant antibody whose target is not a cell surface receptor, as is the case with ADCC. The impact of different types and varying levels of enriched afucosylated N-glycan species on the in vitro bioactivities is assessed for an antibody whose target is aggregated amyloid beta (Aβ). While either the presence of complex biantennary or high mannose afucosylated glycoforms significantly increased FcγRIIIa binding activity compared to fucosylated glycoforms, they did not similarly increase aggregated Aβ uptake activity mediated by different effector cells. These experiments suggest that afucosylated N-glycans are not critical for the in vitro phagocytic activity of a recombinant antibody whose target is aggregated Aβ and uses Fc effector function as part of its MOA.